Nuhṣadumīn sāl-i vafāt-i Khvājah ʻAbd Allāh Anṣārī Haravī : mushtamil bar bayānīyah́hā va maqālāt-i mustashriqīn va barkhī az nivīsandagān-i kishvar, bā muktasarī az jarayān-i sālgirah (Da Millī Difāʻ Maṭbaʻah, 1962)
Commemorative volume on the 900th death anniversary of ʻAbd Allāh ibn Muḥammad Anṣārī al-Harawī, 1006-1089, eminent Afghan Sufi and Persian poet.